1990
DOI: 10.2337/diab.39.9.1017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin Therapy on Metabolic Fate of Apolipoprotein B–Containing Lipoproteins in NIDDM

Abstract: Non-insulin-dependent diabetic (NIDDM) subjects exhibit abnormalities in their plasma lipid and lipoprotein profiles that increase the risk of ischemic heart disease. This study was designed to examine the metabolic behavior of very-low-density (VLDL), intermediate-density (IDL), and low-density (LDL) lipoproteins in NIDDM patients before treatment and after 4 wk of insulin therapy. Basal turnover studies of 131I-labeled VLDL1 (svedberg units [Sf] 60-400) and 131I-labeled VLDL2 (Sf 20-60) apolipoprotein B (apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 0 publications
9
78
2
Order By: Relevance
“…This finding confirms a similar observation made in earlier study using radioiodinated tracers in which the VLDL1 and VLDL2 apo B production rates were 811 ± 233 and 182 ± 253 mg/day respectively [12]. We observed a small decrease in VLDL2 apo B production during the hyperglycaemic clamp.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding confirms a similar observation made in earlier study using radioiodinated tracers in which the VLDL1 and VLDL2 apo B production rates were 811 ± 233 and 182 ± 253 mg/day respectively [12]. We observed a small decrease in VLDL2 apo B production during the hyperglycaemic clamp.…”
Section: Discussionsupporting
confidence: 81%
“…Isolation of lipoproteins. VLDL1 and VLDL2 were isolated from plasma by cumulative flotation gradient ultracentrifugation using a six-step discontinuous salt gradient as previously described [12,13,14]. Pool sizes for apo B were calculated from the product of plasma volume (assumed to be 4.5 % of body weight) times the plasma concentration of apo B in VLDL1 and VLDL2.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of apo B 100 and apo B 48 allows separation of particles from endogenous and exogeneous origins. Reproduced from reference [8] tionally higher increase of VLDL 1 particles compared with VLDL 2 particles in a small group of Type 2 diabetic patients [17]. Likewise another study [18] reported a relatively higher increase of VLDL 1 than that of VLDL 2 particles in a small cohort of Type 2 diabetic subjects.…”
Section: Heterogeneity Of Triglyceride Rich Lipoproteins (Trls)mentioning
confidence: 87%
“…25 The daily food intake was divided into small equal portions taken by the subjects every 2 h, as previously performed by several groups. 7,8 With this protocol plasma lipid and apolipoprotein values remained constant throughout the kinetic study.…”
Section: Discussionmentioning
confidence: 99%
“…Food intake, with a leucine-poor diet (1700 kcal=day, 55% carbohydrates, 39% fats and 7% proteins), was fractionated in to small equal portions which were provided every 2 h, starting 6 h prior to the tracer infusion up to the end of the study, in order to avoid important variations in apolipoprotein plasma concentration, as previously performed by other groups. 7,8 To determine the kinetics of apolipoprotein A-I, the subjects received an intravenous injection of a 0.7 mg=kg bolus of L-[1-13 C]leucine (99% 13 C, Eurisotop, Saint Aubin, France), immediately followed by a 16 h constant infusion at 0.7 mg=kg=h. Blood samples (16 ml) were collected at hours 0, 0.25, 0.75, 1, 1.5, 2, 3, 4, 6, 8, 10, 12, 14, 15 and 16.…”
Section: Experimental Protocolmentioning
confidence: 99%